The Roles of CircRNAs in Bladder Cancer: Biomarkers, Tumorigenesis Drivers, and Therapeutic Targets - Cheng, Fajuan; Zheng, Bin; Si, Shubin; Wang, Jianwei; Zhao, Guiting; Yao, Zhongshun; Niu, Zhihong; He, Wei (Frontiers in Cell and Developmental Biology, 2021)
Bladder cancer (BCa) is the most prevalent malignancy of the urinary system. CircRNAs, a novel subtype of non-coding RNAs, play a crucial role in physiological and developmental processes. . CircRNAs mainly function as regulators of splicing process and transcription, microRNA sponges, protein brackets. Recent advances in understanding the pathogenesis of BCa, have led to the identification of an abundance of dysregulated circRNAs associated with BCa. These aberrantly expressed circRNAs eventually lead to abnormalities in biological, genetic and epigenetic information. In this review, we introduce the potential of circRNAs as biomarkers for BCa diagnosis and prognosis. Notably, diverse mechanisms have been proposed for circRNAs driving carcinogenesis, including increasing cell proliferation, promoting invasive and migratory capacity, enhancing endothelial-mesenchymal translation, sustaining stemness, and enabling resistance to chemotherapy. Importantly, a full understanding of circRNA mechanisms is needed to mine promising therapeutic approaches for targeting BCa. In this paper, we present the latest advances in circRNAs and systemically summarize the characteristics and mechanisms of circRNAs in BCa, providing potential perspectives for BCa treatment.